Estimation of Mammalian Embryos Viability and Efficiency of Their Cryopreservation Technology - Gorbunov, L. V. (Problems of Cryobiology and Cryomedicine, 2003)
To exclude the effect of different quality for embryos on the rate of efficiency estimation as for their cryopreservation technology we propose a relative index for bioobject’s viability alteration, the survival. Using the quantitative method of statistical evaluation in estimation of mammals’ embryos viability rate and determining of the efficiency of their cryopreservation technology allowed to decrease the value of standard deviation error more than twice comparing with a standard method of alternate variation.